PENGARUH MODEL PENGAJARAN INDUKTIF KATA BERGAMBAR TERHADAP KETERAMPILAN MENULIS MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN - Tomasouw, Jolanda (Perspektif Ilmu Pendidikan, 2014)
Inductive word picture teaching model is an instructional model used for the students at beginner level at the German Study Program to direct them to complete the complicated tasks applying higher thinking order. This research aimed at discovering the effect of this model towards the students’ writing skill in German. This experimental research applied single design with pre- and post- tests in Faculty of Teachers Education, Pattimura University, Ambon during the second semester of 2013/2014. The result of research showed, the model has significant influence to writing skill. This means, the model forces the students to think inductively in writing. Besides, the model enables them to construct their basic structural analysis systematically.